Ectoparasites in free-ranging American kestrels in Argentina: Implications for the transmission of viral diseases - Liébana, María Soledad (2011)
We described ectoparasitic species such as chewing lice, mites, and louse flies in free-ranging American Kestrels (Falco sparverius) in the semiarid forest of Argentina. From twenty-two adults and one juvenile American Kestrel captured (fourteen females and nine males) during four breeding seasons between 2005 and 2008, we found in seven birds (six females and one male) two louse species (Laemobothrion tinnunculi and Degeeriella carruthi), one mite species (Ornithonyssus bursa) and one louse fly (Icosta americana). Although the two louse species have been previously reported as parasites of American Kestrels, this is the first record for O. bursa in American Kestrels and the first for I. americana in Argentina. This finding is of particular interest because West Nile Virus (WNV) has been detected in I. americana, which suggests a potential role of this louse fly in the transmission of WNV in raptors in North America. Our results highlight the need for further studies on American Kestrel ectoparasites and also on host-parasite interactions for other neotropical raptors to better understand effects of parasitism on the health of those bird species and to detect possible vectors of infectious diseases.